Ultrastructure of Rickettsia rhipicephali, a new member of the spotted fever group rickettsiae in tissues of the host vector Rhipicephalus sanguineus. - Hayes, S F (1979)
Rickettsia rhipicephali is similar in ultrastructure to R. rickettsii while differing from other rickettsiae of the typhus group and of Q fever and others by its lack of a prominently reticulated cytoplasmic matrix and in the thickness of the inner osmophilic layer of the cell wall. In tissues of the tick vector Rhipicephalus sanguineus, R. rhipicephali had a mean length and width of 1.2 and 0.46 micrometer, respectively. It possessed a trilaminar cell wall with an adhering capsule-like layer. The trilaminar cell wall was approximately 12 to 18 nm thick; its inner osmophilic layer was thicker than that previously reported for other rickettsiae. The capsule-like layer varied from 7 to 18 nm thick. The plasma membrane was similar in structure, measurement, and appearance to that of other reported rickettsiae. The cytoplasm appeared to be composed of a finely granular, amorphous, ground substance and randomly dispersed ribosomes and lacked a reticular matrix or nuclear fibrils. In massively infected salivary glands and ovarial tissues of its tick vector, R. rhipicephali produced a low degree of histopathology which does not appear to affect the engorgement and egg-laying process of the ticks.